The Power of the Chinese Dragon Implications for African Development and Economic Growth - Henson, Spencer; Yap, O. Fiona; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
This important reader brings together published articles from Palgrave's journal The European Journal of Development Research on the development between China and Africa as well as emerging national economies in the BRICs group. Topics include trade relations, investment in sub-Saharan Africa, global politics of development and more.
Keywords: Political economy; International economics; Economic policy; Development economics; Economic growth; Asia -- Economic conditions; Economics; Economic Policy; International Economics; Asian Economics; Development Economics; Political Economy; Economic Growth; Electronic books